Recognition and characterization of potential soft tissue from a fossil ichthyosaur found in the Early Cretaceous (Barremian - Aptian) of Colombia (2025)
The Early Cretaceous of Colombia presents a rich, abundant, and well-preserved fossil vertebrate record of marine reptiles related to the Alto Ricaurte Marine Reptile Lagerstätte. However, despite the growing number of studies on soft tissue preservation worldwide in recent years, few have explored this remarkable preservation in this region. This study aims to identify and characterize the potentially preserved soft-tissue remains in the ichthyosaur specimen CIP-0107, addressing the question of how the taphonomic conditions of the Paja Formation contributed to exceptional soft-tissue preservation. In this context, samples of an Aptian ichthyosaur from the Paja Formation of Colombia were analyzed using techniques such as EDTA demineralization, thin section preparation, transmitted and polarized light microscopy, SEM-EDS, and ATR-FTIR spectroscopy. These analyses revealed net-like structures interpreted as potential keratinized epithelium in the stratum spinosum of epidermis, and skin-like tissues. The findings indicate preservation facilitated by rapid burial in “soupy” sediments, microbial activity, and dysoxic-anoxic marine conditions, and highlights the potential of Colombia as a key region for paleontological studies.